Pengaruh Kepribadian Proaktif, Kompetensi dan Budaya Organisasi Terhadap Kinerja Karyawan Hotel Bintang Empat di Kota Semarang - Aurilia Triani Aryaningtyas (J-MAS (Jurnal Manajemen dan Sains), 2019)
This study examines the effect of proactive personality, competence, and organizational culture on employee performance using data 200 employees of four-star hotels in Semarang. The results show that proactive personality, competence, and organizational culture positively and significantly influence employee performance. The theoretical implications of the research results support both existing theories and research, while managerial implications suggest that organizations / hotels consider proactive personality, competence, and organizational culture as important factors to encourage employees to work effectively to improve their performance.